Break Even Point and Margin of Safety Analysis at Cangkir Pertama Coffee Shop, Purwakarta - Tegar Fazar Ramadhan; Bintang Nidia Kusuma; Muhammad Ali Akbar (Global Writing Academica Researching and Publishing, 2026)
Coffee Shop Cangkir Pertama was a local coffee shop business in Purwakarta operating since 2019, but its financial management remained simple, without a systematic break-even or sales safety margin analysis, so management could not determine the minimum sales volume needed to avoid losses or gauge the safety of its financial condition against a potential sales decline. This study analyzed the minimum sales volume based on the Break-Even Point (BEP), analyzed the sales safety margin based on the Margin of Safety (MOS), and evaluated the level of safety and feasibility of the business through the integration of both methods. This research used a descriptive quantitative method with primary and secondary data on sales and operational costs for the period of March 2025 to February 2026, collected through interviews, observation, and documentation, then analyzed using BEP, MOS, and Contribution Margin calculations. The results showed that the average quarterly BEP was IDR42,533,333 or 1,519 units, with an average MOS of 62.03% and a Contribution Margin Ratio of 75%. Annual revenue of IDR448,476,000 far exceeded the annual BEP of IDR170,133,333, indicating that Coffee Shop Cangkir Pertama was in a healthy, safe, and viable financial condition.